2020
DOI: 10.1080/13614533.2019.1628078
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Evidence-Based Practices to Improve Library Instruction: Using Customized Tools to Support Peer Mentoring and Observation

Abstract: To improve the quality of our instruction, and to contribute to student success, we designed an instructional development program using peer mentoring and observation grounded in evidence-based practices. We identified three methods of peer observation and mentoring to create an innovative progressively in-depth program that helps librarians understand what is happening in the classroom, and works within a community of practice to identify ways to improve the quality of our instruction. These tools, used in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The learning strategy goes with the cognitive approach such as dividing learning material into small portions (chunking), promote repletion to build certain thoughts, and explaining in detail with the intention of increasing memory and understanding. Several strategies that related to cognitive skills in library instruction include conducting online discussions (Tewell 2018;Budai and Williams 2021), critical library instruction (Whitver and Lo 2017;Tewell 2018;Azadbakht, 2019;Tomaszweski 2021), and cognitive apprenticeship (Tomkins 2016;Oberlies, Buxton and Karpinski 2020).…”
Section: C) Cognitivismmentioning
confidence: 99%
“…The learning strategy goes with the cognitive approach such as dividing learning material into small portions (chunking), promote repletion to build certain thoughts, and explaining in detail with the intention of increasing memory and understanding. Several strategies that related to cognitive skills in library instruction include conducting online discussions (Tewell 2018;Budai and Williams 2021), critical library instruction (Whitver and Lo 2017;Tewell 2018;Azadbakht, 2019;Tomaszweski 2021), and cognitive apprenticeship (Tomkins 2016;Oberlies, Buxton and Karpinski 2020).…”
Section: C) Cognitivismmentioning
confidence: 99%
“…The results indicated that the use of students’ self-reported IL needs is critical for developing IL courses which are relevant to learners. Oberlies, Buxton and Zeidman-Karpinski (2020) tested Teaching Squares (TS), the Teaching Practices Inventory (TPI) and the Classroom Observation Protocol (COP) to inform improvement of IL instructions offered to the undergraduate students. The tools were found to be effective in helping instructors to refine and develop IL instructions to learners.…”
Section: Related Literaturementioning
confidence: 99%